2015
DOI: 10.1002/bmc.3626
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic routes along digestive system of licorice: multicomponent sequential metabolism method in rat

Abstract: This study was conducted to establish the multicomponent sequential metabolism (MSM) method based on comparative analysis along the digestive system following oral administration of licorice (Glycyrrhiza uralensis Fisch., leguminosae), a traditional Chinese medicine widely used for harmonizing other ingredients in a formulae. The licorice water extract (LWE) dissolved in Krebs-Ringer buffer solution (1 g/mL) was used to carry out the experiments and the comparative analysis was performed using HPLC and LC-MS/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The results suggested that liquiritin in GRE could be a precursor for isoliquiritigenin and liquiritigenin and is a more potent pharmacological component [25]; therefore, the hydrolysis of liquiritin could be attributed to an increased plasma concentration of isoliquiritigenin and liquiritigenin during the absorption period (from 4 to 10 h in this study). The results were consistent with the previous report that isoliquiritigenin and liquiritigenin, which were generated from liquiritin, were absorbed from the jejunum to colon with the help of gut wall enzymes and intestinal flora [26].…”
Section: Discussionsupporting
confidence: 93%
“…The results suggested that liquiritin in GRE could be a precursor for isoliquiritigenin and liquiritigenin and is a more potent pharmacological component [25]; therefore, the hydrolysis of liquiritin could be attributed to an increased plasma concentration of isoliquiritigenin and liquiritigenin during the absorption period (from 4 to 10 h in this study). The results were consistent with the previous report that isoliquiritigenin and liquiritigenin, which were generated from liquiritin, were absorbed from the jejunum to colon with the help of gut wall enzymes and intestinal flora [26].…”
Section: Discussionsupporting
confidence: 93%
“…The complex surgical procedure and the in situ closed-loop experiments were conducted in accordance with the methods described previously [20,23]. The rats were divided into two groups.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the primary goal of this study was to develop a holistic, sequential and reproducible approach to describe the complicated sequential metabolism of salidroside before absorption into the systemic blood stream. In brief, the approach includes four fundamental steps: (1) enzymatic transformation in digestive juice, (2) biotransformation by intestinal flora tract, (3) gut wall metabolism, and (4) hepatic metabolism [20]. The approach was based on comparative analysis and a carefully designed mix of metabolic techniques such as in vitro incubation, in situ closed-loop and in vivo blood sampling.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 However, the gastrointestinal metabolic profile of the Cistanches Herba water extract, which is frequently administered orally, may be absolutely different from that of the individual compounds because of competitive effects and exposure to components at different concentrations. 6,16 Additionally, polysaccharides and oligosaccharides that are present in the Cistanches Herba water extract are potential sources of prebiotics, which may affect the composition of intestinal microbiota and in turn influence the metabolic profile of Cistanches Herba. 17 Hence, it becomes extremely necessary to elucidate the human gastrointestinal metabolism of the Cistanches Herba water extract, i.e., the stems of CD and CT. Four in vitro incubation models, including simulated gastric juice (GJ), simulated intestinal juice (IJ), human intestinal bacteria (HIB), and human intestinal microsomes (HIM), were employed independently and sequentially to investigate the bioconversion of the Cistanches Herba water extract in the stomach, intestine, gut microbiota, and gut wall.…”
Section: ■ Introductionmentioning
confidence: 99%